A study on public servant perceived level of readiness in implementing the Government Transformation Programme (GTP): a case study in ministry of rural and regional development Kuching, Sarawak / Frederick Vinu and Willie Watson Awan - Vinu, Frederick; Watson Awan, Willie (2013)
This chapter focuses on the general backgrounds of the studies, which is concerning the perceived perception of the public servants regarding their level of readiness in implementing Government Transformational Programme (GTP). Section 1.1 will discuss about the background of the study. Meanwhile section 1.2 will explain about the background of Ministry of Rural and Regional Development (MRRD) in Kuching and 1.3 is about the problem statement. Section 1.4 on the other hand, states the research questions. Section 1.5 is regarding the research objective and section 1.6 is the scope of the study. Followed by section 1.7 is regarding the hypothesis and continue with section 1.8 explains the significance of the study. Lastly, section 1.9 is regarding the definitions of terms/concepts.